2004
DOI: 10.1111/j.1365-2036.2004.02009.x
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine dose escalation in inflammatory bowel disease

Abstract: Increasing the azathioprine dose up to 2.5 mg/kg/day appears beneficial in patients who have not responded to 2 mg/kg/day. Further increase above 2.5 mg/kg/day is less likely to be efficacious, and is associated with a substantial risk of adverse reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Thiopurines (azathioprine and 6-mercaptopurine) have been found to be superior to placebo in maintaining remission in distal UC [19,20] . Overall, oral therapy with azathioprine or 6-mercaptopurine is reserved for patients with steroid-dependent distal UC and those with chronic disease that is refractory to other drugs.…”
Section: Maintenance Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiopurines (azathioprine and 6-mercaptopurine) have been found to be superior to placebo in maintaining remission in distal UC [19,20] . Overall, oral therapy with azathioprine or 6-mercaptopurine is reserved for patients with steroid-dependent distal UC and those with chronic disease that is refractory to other drugs.…”
Section: Maintenance Treatmentmentioning
confidence: 99%
“…Patients with early stage disease have higher steroid-free remission rates on azathioprine compared to patients with late stage disease [21] . Moreover, it has been suggested that increasing the dose of azathioprine up to 2.5 mg/kg appeared beneficial in patients who had not responded to 2 mg/kg per day [20] . The use of azathioprine in distal UC is less indicated than in extensive UC.…”
Section: Maintenance Treatmentmentioning
confidence: 99%
“…However, in Japan, low doses (50–100 mg daily) of AZA are recommended because Japanese patients are more susceptible to dose-dependent adverse events [10]. Although a higher dose of AZA has been observed to produce better effects than a lower dose [11], it is not clear whether in Asian patients low-dose (50–100 mg daily) AZA is as effective as the standard dose for long-term maintenance of remission. In China, where the incidence of CD is rapidly rising, the number of patients dependent on immunomodulators has increased over the years [12].…”
Section: Introductionmentioning
confidence: 99%
“…Non-responders to low doses will benefit from dose escalation to AZA 2–2.5 mg/kg/day2022 but benefit of dose escalation above this level is less 23. Target doses should be adjusted using TPMT levels, as shown in table 1.…”
Section: Pharmacology and Pharmacogeneticsmentioning
confidence: 99%